2020
DOI: 10.1016/j.jid.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Inducible MAPK/AP-1 Signaling Drives Semaphorin 3A Expression in Normal Human Epidermal Keratinocytes

Abstract: Epidermal keratinocytes are primarily involved in the expression of semaphorin (Sema) 3A, which is involved in the regulation of cutaneous innervation. However, the mechanisms underlying the intracellular signaling of Sema3A expression in keratinocytes remain unknown. We herein investigated the signaling mechanisms for the induction of Sema3A expression in normal human epidermal keratinocytes (NHEKs). Sema3A expression is transiently increased in calcium-stimulated NHEKs, whereas it is markedly decreased in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Nrp1 is upregulated in primary keratinocytes in response to differentiating media [ 13 ]. Sema3A represses neurogenesis via Nrp1, and also plays an important role in keratinocyte migration and differentiation [ 26 , 27 , 28 ]. Our previous study demonstrated that Sema3A and kCer do not affect histamine-GPCR-mediated cell migration and undifferentiation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nrp1 is upregulated in primary keratinocytes in response to differentiating media [ 13 ]. Sema3A represses neurogenesis via Nrp1, and also plays an important role in keratinocyte migration and differentiation [ 26 , 27 , 28 ]. Our previous study demonstrated that Sema3A and kCer do not affect histamine-GPCR-mediated cell migration and undifferentiation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The culture medium was replaced with antibiotic-free medium and the cells were co-transfected with 500 ng/well pGL3-Sema3A vector containing the firefly luciferase gene and 50 ng/well pRL3-TK vector containing the Renilla luciferase gene (Promega, Madison, WI, USA) using X-tremeGENE HP DNA Transfection Reagent (Roche Diagnostics GmbH, Mannheim, Germany) in accordance with the manufacturer's instructions. pGL3-Sema3A vector was produced in accordance with the methods reported by Kamata et al [14]. At 24 hours after the start of transfection, the medium was replaced with fresh medium containing the test samples shown in Table 1, apigenin, baicalein, baicalin, chrysin, or wogonin (Wako Pure Chemical Industries, Ltd., Osaka, Japan) at various concentrations, and NHEKs were further incubated for 24 or 48 hours at 37˚C.…”
Section: Transfection and Measurement Of Promoter Activitymentioning
confidence: 99%
“…Cultured NHEKs were transfected with luciferase reporter gene constructs containing -1444 bp of the human Sema3A promoter as described previously [14]. Following transfection, cells were treated with various types of herbal plant extracts at a final concentration of 50 μg/mL for 24 hours and the cell lysates were subjected to luciferase assays.…”
Section: Screening Of Sema3a Inducers From Herbal Plant Extracts Using a Reporter Gene Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Sema3A is reported to mainly localize in the keratin14-positive keratinocytes in the stratum basale 127 of the human epidermis 27 . Therefore, to investigate the role of Sema3A in Ni allergy in vivo, we crossed Sema3A fl/fl mice with keratin5 (K5)-Cre mice using a cre/loxp system to knockout Sema3A in K5, which is a similar protein and partner of keratin14.…”
Section: Sema3a-specific Deletion In Keratinocytes Reduces Ni Allergymentioning
confidence: 99%